EMPLOYMENT OF RESOURCES ON ADEQUATE MEASURE: A COMPUTATIONAL TOOL FOR AGRICULTURAL OPTIMIZATION - Cavalcante, Jose Airton Chaves (2012)
The present article is presented in VII CNEG 2011 and was expanded. This paper describes a computational tool developed for agriculture - SIPRABAL (Integrated Production System and Maximizated Agricultural Revenue with balance on soil). This system has taken part on research related to course for elaboration of thesis on binational (PhD on Agromathmatics at UFRRJ - Federal University of Rio de Janeiro,Brazil and URNC - Rio Cuarto National University,Argentina). The main purpose of the project has been the composition of a computational code, in according to “user friendly” philosophy; therefore increasing probabilities for an easier access to the user, even for those ones not so experts on computer handling, at all. Input complex data will be used by the system, as well as, will computationally be accumulated, allowing to choose among available productive resources utilization, satisfying certain pre-established aims related to soil, humidity and environment, disposing results to low income farmers, in order to clearly and directly answering them, as well. This sort of system can be employed on limited resources situations, supporting the smallholder on his making decision and providing him effective methods and information. Taking into account that farming activities managements demands technical and financial knowledges, the purpose of SIPRABAL as a product of technological innovation has been sharing on farming making decisions whereabouts economical analysis and rational use of available resources (water, fertilizers, land, etcâ¦) have been relevant. Increasement of the effectiveness on water use, selected cultures yield for an adequate tillage and production costs decreasement maximizing investments on farming irrigation through an accessible system utilization to the peasant it might be expected, as well.